Pelatihan Penghitungan PPH Pasal 21 dan SPT Orang Pribadi - Lukmanul Hakim; Achmad Sehan (Prisani Cendekia, 2023)
Community service as one of the pillars of higher education occupies a strategic position in drawing and educating the community to improve the quality of life of the community. The form of coaching that is considered the most realistic is none other than providing provision through skills training and mentoring that is considered useful for the local community audience. The low awareness of taxpayers to comply with taxes is the biggest problem faced by the Directorate General of Taxes (DGT) while the government's largest source of funds to finance development is obtained from tax collection, the mechanism of which is coercive in accordance with Indonesian laws and regulations The desire to change people's mindset to be aware of taxes with early education requires systematic technical means, one of which is through inclusion in learning materials and training activities for various groups including private workers or private employees. The implementation method is the counseling method, by going through the preparation stage, the implementation stage and the results stage. Based on the results of the PKM team's observations during the activity, the interest from private employees towards the material provided was very high. The enthusiasm of the participants and the average participant were active in listening to the counseling material. This observation is shown by the high curiosity of private employees so that many questions are asked to the informants. The activity of the resource persons who also asked questions to the participants how far they knew taxation was shown by the many questions asked in the PKM counseling